Open Innovation at Different Levels for Higher Climate Risk Resilience. (November 2017) - Dey, Anamika; Gupta, Anil; Singh, Gurdeep
With the increase in climate variability, creating knowledge networks becomes important for leveraging the embedded resilience in the communities through cross-pollination of ideas, resources and institutional linkages. Communities have developed knowledge systems around climate-mediated environmental changes since time immemorial. Some social groups have capacity to cope with stress better. They have homeostatic advantage due to either accumulated surplus (Burton, 2001, Vulnerability and adaptation to climate change in the drylands, United Nations Environment Programme) or access to institutions, technology and social networks (Adger, 2003, Social capital, collective action, and adaptation to climate change. Economic Geography, 79(4), 387–404). However, these knowledge systems often remain limited as isolated islands of expertise or small local networks resulting into asymmetries of knowledge at inter- or intra-community level. Intermediary organisations/platforms become important to bridge the gap that exists among communities within the informal sector and also between the formal and informal sectors. The platforms like the Honey Bee Network (henceforth, the Network) have been able to facilitate both horizontal exchanges, people-to-people learning and sharing, and vertical exchanges, connecting the informal actors with the formal system. The variation in different components of an Open Innovation System is studied in this article through their degree of openness in sharing, self-governance and self-regulation. We explore different activities and institutions of the Network to study the degree of openness and how they contribute to make the 26-year-old ecosystem more sustainable. We draw lessons for other institutions, organisations, communities who strive towards an autopoietic system, that is, a self-designed, self-organised and self-governed system with a feedback system from within and outside. This may make the whole innovation and knowledge ecosystem resilient in dealing with changing climatic conditions and fluctuating environment.